Teachers' Creativity in Increasing Students' Interest in Learning in Educational Institutions in Rw 06 Petukangan Selatan - Rika Handayani; Taufiq Ramadhan; Azmi Islami; Dinda Imroatul Azizah (Universitas Darunnajah, Jakarta, Indonesia, 2023)
Abstract: A teacher is required to be more creative in processing the learning process into something unique and interesting. Teaching creativity is defined as a quality in which teachers must develop new and imaginative ideas in teaching. Therefore, a creative response in teaching can be in the form of good classroom management that can create a conducive learning atmosphere, the use of interesting learning media, and variations in teaching styles. Real Work Lecture (KKN) is a concrete manifestation of the duties of lecturers and students in carrying out the Tri Dharma of Higher Education, namely the aspect of service. Through community service activities in the RW 06 area, Petukngan Selatan, there is a synergy between universities and the community as a form of democratic knowledge. The purpose of this service is to provide understanding to the local community about the importance of education to assist the government in educating the nation's children. Service is carried out through activities: Teaching KKN. The results of the service provide an illustration of increasing enthusiasm and increasing public understanding, especially teachers and parents, about how to foster creativity in educating, educational psychology, the importance of reading for children, tutoring and making learning media for teachers as materials for teaching in monotheism-based classes.